Physical activity patterns and biomarkers of cardiovascular disease risk in hunter‐gatherers. Issue 2 (9th October 2016) - Raichlen, David A.; Pontzer, Herman; Harris, Jacob A.; Mabulla, Audax Z. P.; Marlowe, Frank W.; Josh Snodgrass, J.; Eick, Geeta; Colette Berbesque, J.; Sancilio, Amelia; Wood, Brian M.
Abstract: Objectives: Time spent in moderate‐to‐vigorous physical activity (MVPA) is a strong predictor of cardiovascular health, yet few humans living in industrialized societies meet current recommendations (150 min/week). Researchers have long suggested that human physiological requirements for aerobic exercise reflect an evolutionary shift to a hunting and gathering foraging strategy, and a recent transition to more sedentary lifestyles likely represents a mismatch with our past in terms of physical activity. The goal of this study is to explore this mismatch by characterizing MVPA and cardiovascular health in the Hadza, a modern hunting and gathering population living in Northern Tanzania. Methods: We measured MVPA using continuous heart rate monitoring in 46 participants recruited from two Hadza camps. As part of a larger survey of health in the Hadza, we measured blood pressure ( n = 198) and biomarkers of cardiovascular health ( n = 23) including C‐reactive protein, cholesterol (Total, HDL, and LDL), and triglycerides. Results: We show that Hadza participants spend large amounts of time in MVPA (134.92 ± 8.6 min/day), and maintain these activity levels across the lifespan. In fact, the Hadza engage in over 14 times as much MVPA as subjects participating in large epidemiological studies in the United States. We found no evidence of risk factors for cardiovascular disease in this population (low prevalence of hypertension across the lifespan, optimal levels for biomarkers of cardiovascular health). Conclusions: Our results provide evidence that the hunting and gathering foraging strategy involves high levels of MVPA, supporting the evolutionary medicine model for the relationship between MVPA and cardiovascular health.